Pola Perilaku Pengguna Situs Judi Online dan Faktor-Faktor yang Mempengaruhi - Junita Friska; Adita Hervani Br Barus; Alfyanti Alfyanti; Dianrani Anastasya Purba; Ika Novita Padang; Jenni Romayanti Ginting (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
Online gambling requires risking money and valuables for an uncertain return.Currently, online gambling is increasingly favored by everyone, from the elderly to the youth, because online gambling can be easily accessed by anyone anytime and anywhere. Online gambling also has a negative impact on the lives of adolescents, including decreased academic achievement, emotional instability, poor relationships with others, and gambling disorders.The purpose of this study is to identify factors that influence online gambling behavior among young people. Based on the results of the quantitative study, five main categories were identified: factors originating from the individual, family, social environment, socioeconomic factors, and Internet characteristics. This quantitative research is expected to provide readers with comprehensive information about the factors that encourage adolescents to engage in and maintain online gambling, as well as help address the situation to prevent the negative impact of online gambling and this can be the basis for developing interventions to raise awareness. Young people, especially those who intend not to gamble anymore and choose to participate in activities that are beneficial to their future opportunities, should be aware of the importance of online gambling.